2013
DOI: 10.2139/ssrn.2366519
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and Savings

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…() additionally observe that a positive personal experience with annuities/stocks increases the demand for the respective investment, while Cobb‐Clark et al. () find that individuals with an internal locus of control tend to hold more pension wealth . Finally, Goedde‐Menke et al.…”
Section: Three Aspects Of Annuitization Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…() additionally observe that a positive personal experience with annuities/stocks increases the demand for the respective investment, while Cobb‐Clark et al. () find that individuals with an internal locus of control tend to hold more pension wealth . Finally, Goedde‐Menke et al.…”
Section: Three Aspects Of Annuitization Decisionsmentioning
confidence: 99%
“…Locus of control is a concept that describes the attitude of an individual regarding the outcomes of her own behavior on life events (Cobb‐Clark et al., , p. 113). A person with an internal locus believes that she can control her life, whereas the external locus means that life is believed to be determined by external factors.…”
mentioning
confidence: 99%
“…Cobb‐Clark et al . (), for example, show that locus of control is linked to savings (those who believe that they can control relevant aspects of life save more). Extroversion has been linked to short‐term investing, neuroticism has been linked to risk aversion, openness to experience has been linked to long‐term investing, and conscientiousness has been linked to saving (for a review of the personality and finance literature see Killins, ).…”
Section: Previous Researchmentioning
confidence: 99%
“…Studies in this area have shown that people who have internal locus of control tend to invest more in human capital accumulation than people with an external locus of control, because the former’s expected return to human capital investment is higher (Coleman and DeLeire, 2003). 1 People with internal locus of control also tend to live a healthier lifestyle through healthier diets and exercise (Cobb-Clark et al, 2014), save more money for “rainy days” (Cobb-Clark et al, 2013), invest more time to stimulate cognitively their children (Lekfuangfu et al, 2014), and hold riskier assets (Salamanca et al, 2013). Another interesting and important property of internal locus of control is grit or perseverance in the face of adversity.…”
Section: Introductionmentioning
confidence: 99%